Incidence of thyroid cancer in England by ethnic group, 2001-2007 - Finlayson, A; Barnes, I; Sayeed, S; McIver, B; Beral, V; Ali, R (Nature Publishing Group, 2014)
Background: Thyroid cancer incidence is increasing worldwide, but with large variations in incidence that may reflect either diagnostic bias or true ethnic differences. We sought to determine the effect of ethnicity on the incidence of thyroid cancer in England, a multiethnic population with a single health-care system. Methods: We analysed 11 263 thyroid cancer registrations with ethnicity obtained by linkage to the Hospital Episodes Statistics database. Incidence rate ratios (RRs) adjusted for age, sex and income were calculated for the six main non-White ethnic groups in England compared with Whites and to each other. Results: Thyroid cancer incidence was higher in all ethnic groups, except Indians, compared with Whites: in Pakistanis (RR 1.79, 99% floating confidence interval (FCI) 1.47-2.19); Bangladeshis (RR 1.99, 99% FCI 1.46-2.71); Black Africans (RR 1.69, 99% FCI 1.34-2.13); Black Caribbeans (RR 1.56, 99% FCI 1.25-1.93); and Chinese (RR 2.14, 99% FCI 1.63-2.80). Conclusion: The risk of thyroid cancer in England varies significantly by ethnicity. The elevated incidence in most ethnic minorities is unlikely to be due to diagnostic bias and warrants further investigation. © 2014 Cancer Research UK.